2017
DOI: 10.1002/polb.24409
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on spreading of water nano‐droplet on poly(methyl methacrylate): A molecular dynamics simulation study

Abstract: In this article, the effect of temperature on the spreading behavior of a water nano‐droplet on poly(methyl methacrylate) substrate is investigated. The contact angle analysis illustrates that the spreading process occurs in a stage‐like manner and the increase in temperature causes a regime change from partial to total wetting. The interaction energy distributions show that there exist sites on the surface which could trap water molecules and provide a better path for other molecules to overcome the asperitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Furthermore, it can be observed that the CA values decrease as the temperature rises in both 3 and 22.5 ns simulations. A similar behavior on hydrophilic poly­(methyl methacrylate) was recently reported by our team, which is line with the acquired results . Following the discussion regarding the TPCL and CA behaviors, evaporation and condensation processes can now be studied further.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, it can be observed that the CA values decrease as the temperature rises in both 3 and 22.5 ns simulations. A similar behavior on hydrophilic poly­(methyl methacrylate) was recently reported by our team, which is line with the acquired results . Following the discussion regarding the TPCL and CA behaviors, evaporation and condensation processes can now be studied further.…”
Section: Resultssupporting
confidence: 90%
“…It can be observed that the height of the peaks decreases as the temperature increases in both systems. This is related to the simultaneous occurrence of spreading as well as evaporation . The only exception to the results occurs for the fixed substrate at 500 K. High temperature has caused the droplet to be completely evaporated even though an interfacial layer of water molecules can still be distinguished.…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Despite the many studies that have been done on the water and MoS 2 system, some surface tips of the system have not yet been considered. On this premise, we have chosen different surfaces such as Au (1 0 0) [34], TiO 2 (1 1 0) [35], graphene [36], graphene oxide [37] and some polymers [38] to investigate the behavior and interaction of water nano-droplets with them. Our aim contents, therefore, are of interest in order to understand the behavior of water nano-droplets when physisorbed on different substrates.…”
Section: Introductionmentioning
confidence: 99%